2018
DOI: 10.1513/annalsats.201801-028fr
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Pain Management in Patients Affected by the Opioid Epidemic: A Review

Abstract: The rapid rise in the opioid epidemic has had a deleterious impact across the United States. This increase has drawn the attention of the critical care community not only because of the surge in acute opioid overdose-related admissions, but also due to the increase in the number of opioid-dependent and opioid-tolerant patients being treated in the intensive care unit (ICU). Opioid-related issues relevant to the critical care physician include direct care of patients with opioid overdoses, the provision of suff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Similarly, this study revealed a higher prevalence of anxiety disorder for females (42.8%) than for males (25.5%). A recent study reported that 18% of trauma patients have an OUD (Hsiang et al, 2019), while another study suggested that new persistent opioid use was common among patients with chronic pain after minor and major surgeries in U.S. adults (Brummett et al, 2017), which suggests that we should pay more attention to the rapid rise in the opioid epidemic because of the surge in acute opioid overdose-related admissions, but also chronic opioid-dependent and opioid-tolerant patients (Karamchandani et al, 2018). These findings prompt further research designed to test these gender differences in mechanisms of comorbidity, and perhaps particularly those that help explain and understand the elevated associations.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, this study revealed a higher prevalence of anxiety disorder for females (42.8%) than for males (25.5%). A recent study reported that 18% of trauma patients have an OUD (Hsiang et al, 2019), while another study suggested that new persistent opioid use was common among patients with chronic pain after minor and major surgeries in U.S. adults (Brummett et al, 2017), which suggests that we should pay more attention to the rapid rise in the opioid epidemic because of the surge in acute opioid overdose-related admissions, but also chronic opioid-dependent and opioid-tolerant patients (Karamchandani et al, 2018). These findings prompt further research designed to test these gender differences in mechanisms of comorbidity, and perhaps particularly those that help explain and understand the elevated associations.…”
Section: Discussionmentioning
confidence: 99%
“…The primary outcome of the study is total daily opioid dose in fentanyl equivalents (100 mcg fentanyl = 2.5 mg intravenous (IV) methadone = 5 mg oral (PO) methadone = 1.5 mg IV hydromorphone = 7.5 mg PO hydromorphone = 10 mg IV morphine = 20 mg oxycodone = 30 mg hydrocodone 10,11 ) while on ECMO. Secondary outcomes include total daily propofol dose and total daily benzodiazepine dose in midazolam equivalents (1 mg IV lorazepam = 1 mg PO lorazepam = 3 mg IV midazolam = 5 mg IV diazepam 12 ) while on ECMO.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with OUD and opioid tolerance, multimodal analgesia is necessary to properly manage pain, including nonsteroidal anti-inflammatory drugs (NSAIDs), acetaminophen, tricyclic antidepressants, and anticonvulsants (gabapentin), combined with nonpharmacological interventions. In addition, to suppress opioid withdrawal symptoms, α2 adrenergic agonists (e.g., clonidine and dexmedetomidine) or NMDA receptor antagonists (e.g., ketamine) can be administered [2].…”
Section: Opioid Vaccination: a New Hopementioning
confidence: 99%